Progress in AMS Measurement of 182Hf at CIAE - 董克君 何明 李振宇 王祥高 李朝历 游曲波 包轶文 武绍勇 沈洪涛 管永精 张伟 凡金龙 杨磊 孙宏清 丁有钱 贺国珠 李世琢 龚杰 何贤文 陆丽燕 王伟 胡跃明 袁坚 张生栋 常永福 姜山 (Chinese physics letters, 2010)
Accelerator mass spectrometry （AMS） is one of the most promising methods to detect minute amounts of 182Hf. However, the sensitivity of 5×10^-11 for ^182Hf/180Hf obtained previously by the AMS method at China Institute of Atomic Energy （CIAE） cannot meet the requirement of some applications. We present some new improvements of measurement method for AMS measurement of 182Hf at the CIAE HI？13 tandem accelerator system. As a result, a sensitivity of 1.0×10^-11 for 182Hf/180Hf is achieved.